"The Impact of National Culture on Knowledge Sharing: The Moderate Role of Organizational Culture" - Al Thnayan, Saleh; Alarifi, Areej (The Arab Journal of Administration, 2024)
Purpose: Examine the impact of national culture based on Hofstede’s concept of cultural dimensions on knowledge sharing and the moderate role of the organizational factors as success factors. Design methodology approach: The descriptive and inferential approach relying on a simple random sample among local and international employees working in Saudi Arabian Military Industries (SAMI) company. An electronic questionnaire distributed for this purpose. Findings: Collectivism, Femininity, LO, and SR are positively impact on KS, while PD, I, M, UA, SO, and ID are negatively impact the KS. Moreover, OC play a moderate role as success factor to maximize the advantage of PD, C, F, LO and SR and minimize the impact of I, M, UA, SO and ID on KS. In addition, the index of six national cultural dimensions of the sample understudy was compared to original Hofstede index and resulted on almost the same values. Originality / value: There are a few studies that examine the effect of the indulgence/self-restraint dimension. Moreover, most studies focus on single culture and there are a few studies that compare the national culture between two or more countries. Finally, there is no study has been conducted to examine the moderate role of organizational culture in this relationship. All of these aspects give uniqueness to this study and encourage to fill-up those gaps.